SABERES PARA ENSINAR GEOMETRIA NO ENSINO PRIMÁRIO: um estudo sobre manuais escolares produzidos por Theobaldo Miranda Santos - ALINE SUEMI MOROTO (2021)
This research aims to analyze, from a historical perspective, possible knowledge for teaching geometry in Brazilian primary education present in scholar manuals produced by the educator Theobaldo Miranda Santos between 1946 and 1960. The period of time includes the publication of Organic Law of Normal School in 1946 and the year of publication of the most recent teaching manual analyzed. The study was conducted based on the following question: What knowledge for teaching geometry in primary education may be identified in scholar manuals by Theobaldo Miranda Santos and published between 1946 and 1960? We assume the perspective of cultural history (CHARTIER, 2002), and the concepts of scholar culture (JULIA, 2001) history of books and didactic editions (CHOPPIN; 2002, 2004), knowledge to teach and knowledge for teaching (HOFSTETTER; SCHNEUWLY, 2017). We analyzed the teaching manuals Noções de Didática Especial (1960) and Metodologia do Ensino Primário (1952) and the textbooks Vamos Estudar?, produced between 1953 and 1968. The result of the study indicates that the school manual, a cultural product of a given society, reflects the educational purposes of its time. Theobaldo Miranda Santos, a carioca educator with influences from traditional education, may have transitioned between the intuitive wave and the new school and introduced in his teaching manuals knowledge for teaching geometry, knowledge that is also present in his series of textbooks for primary education. The books above not only came to help primary school teachers exercise their educational function, but also gathered and systematized knowledge to be mobilized by teaching professionals.